Peelu (Salvadora oleoides Decne.): An Unexplored Medicinal Fruit with Minerals, Antioxidants, and Phytochemicals. (14th October 2022) - Razzaq, Kashif; Sadiq, Muhammad Muzzammal; Ashraf, Hashir; Naz, Ambreen; Hussain, Abid; Maqbool, Amir; Altaf, Muhammad Tanveer; Ullah, Sami; Akhtar, Gulzar; Faried, Hafiz Nazar; Amin, Muhammad; Rajwana, Ishtiaq Ahmad; et al.
Abstract : The Peelu ( Salvadora oleoides Decne.) fruit is well known for its nutritional and medicinal values. The current study analyzed the chemical composition of Salvadora oleoides fruit. Fresh Peelu fruits were harvested, and physicochemical properties, proximate composition, macro- and micronutrients, and phytochemical properties were determined. Moreover, ethanol and methanol fruit extract was analyzed for physicochemical properties. The Peelu fruit seemed to be a potential source of essential macro- ((nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), and magnesium (Mg)) and micronutrients (zinc (Zn), manganese (Mn), iron (Fe), and copper (Cu)). The fruit had significant biochemical properties (total soluble solids (TSS), total acidity (TA), and TSS : TA ratio) with appreciable moisture, crude fiber, and ash contents. The fruit extracts demonstrated significantly higher antioxidants and phenolics, ascorbic acid contents, and carotenoids. Phytochemical screening of fruit revealed the presence of coumarins, flavonoids, phlobatannins, tannins, and terpenoids. Physicochemical and sensory evaluation of extracts indicated its potential for further in vivo study trials. The Peelu fruit was found to be a good source of mineral nutrients, proximate contents, vitamins (ascorbic acid and carotenoid), phytochemicals (total phenolic sand antioxidant contents), and pharmaceutically important metabolites that can be used as functional drink.